Preparation method of rare earth element-doped PI wave-absorbing foam
By doping rare earth elements and spiral carbon fibers in PI foam and adopting special pretreatment technology, the problem of insufficient absorption and mechanical properties of PI wave absorbing foam materials in the existing technology is solved, and excellent absorption and significant mechanical properties are achieved in the high frequency band and wide frequency band range.
Patent Information
- Application Number
- CN202510286385.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-12
AI Technical Summary
The prior art is difficult to effectively improve the absorbing performance and mechanical properties in PI wave-absorbing foam materials, and there are problems of high production costs and poor thermal stability.
By doping rare earth elements and spiral carbon fibers in the PI foam, special pretreatment technology is used to enhance the permeability of rare earth elements and nickel elements. Combining the rare earth doping technology and the excellent performance of spiral carbon fibers, PI absorbing foams with excellent absorption and mechanical properties are prepared.
It has achieved excellent absorbance performance in high frequency band and wide frequency band range, significantly improved compression strength and thermal stability, and relatively reduced production costs.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of microwave-absorbing foam materials, and in particular relates to a method for preparing rare earth element-doped PI microwave-absorbing foam. Background Art
[0002] Absorbing foam material is a material that absorbs and dissipates sound or electromagnetic wave energy. It is widely used in sound insulation, stealth, electromagnetic compatibility and other fields. Polyimide (PI) foam, as a high-performance material, has broad application prospects in aerospace, electronic information, transportation and other fields due to its excellent thermal stability, good mechanical properties, low dielectric constant and excellent flame retardant properties.
[0003] The durability of the absorbing foam material is affected by the material properties. Long-term use may cause aging and degradation, reducing the absorbing effect. This means that in long-term use, the stability of the absorbing performance of the foam material must be high. Low-quality absorbing foam materials may contain harmful substances, causing potential harm to human health and the environment. Therefore, when preparing absorbing foam materials, special attention should be paid to their environmental protection and safety; the preparation method of special absorbers currently under study is complicated and requires precise control of various parameters. Adding high-performance absorbers will further increase production costs, and the thermal stability and corrosion resistance are poor; therefore, it is very necessary to develop an absorbing foam material containing easy-to-prepare absorbing additives and having good heat resistance and corrosion resistance.
[0004] Rare earth elements are widely used in the field of materials science due to their unique physical and chemical properties. Adding rare earth elements to PI foam can further improve the performance of PI foam by changing the molecular structure of the foam, improving the thermal stability of the foam, and improving the electromagnetic properties of the foam. Research on doping rare earth gadolinium in PI absorbing materials has attracted much attention. However, gadolinium oxide itself does not have significant electromagnetic wave absorption performance. Directly using it in absorbing foam materials cannot effectively improve the absorbing performance of PI absorbing foam. However, as a rare earth oxide material, under certain specific conditions, especially when compounded with other materials, the magnetic properties of gadolinium oxide cooperate with the dielectric properties of other materials to effectively absorb electromagnetic waves, thereby showing absorbing characteristics. It can be seen that in the field of PI foam absorbing materials, the research on doping of rare earth gadolinium elements has shown the potential to significantly improve the absorbing performance of materials.
[0005] As a high-performance fiber material, carbon fiber is often used to reinforce polymer-based composite materials due to its high strength, high modulus, low density and other properties; adding carbon fiber to PI foam can significantly improve the mechanical properties, thermal stability and electrical conductivity of the foam; by adding carbon fiber to PI foam, the tensile strength and compressive strength of the foam can be significantly improved while maintaining good thermal stability and corrosion resistance; using carbon fiber and rare earth elements to prepare absorbing foam materials has important research significance.
[0006] After searching, the applicant did not find any relevant literature or patents on the use of rare earth elements and carbon fibers in the preparation of PI absorbing foam materials. During the research process, the applicant found that the miscibility of rare earth gadolinium and carbon fibers is poor, which will affect the mechanical properties and absorbing properties of the absorbing foam materials, and also affect the stability of the product.
[0007] Therefore, providing a method for preparing a rare earth element-doped PI absorbing foam material, wherein the prepared PI absorbing foam material has good absorbing properties, good mechanical properties, and excellent stability is a technical problem that needs to be urgently solved in the prior art. Summary of the invention
[0008] In order to solve the technical problems existing in the prior art, the present invention provides a method for preparing PI absorbing foam doped with rare earth elements. The method combines the rare earth doping technology and the excellent performance of spiral carbon fiber. The prepared PI absorbing foam has good absorbing performance, good mechanical properties and excellent thermal stability.
[0009] In view of the above technical problems, the present invention adopts the following technical solutions: A method for preparing a rare earth element-doped PI wave-absorbing foam comprises the steps of pre-treating spiral carbon fibers, preparing a PI foam precursor, preparing a clear and transparent viscous solution, foaming, and post-treating. The specific operations are as follows: 1. Pretreatment of spiral carbon fibers (1) Preparation of spiral carbon fibers The Sn-MOF was crushed into 140-160 mesh, mixed with anhydrous ethanol, and ultrasonically dispersed to obtain a suspension; a nickel sheet was placed in the suspension with a mass of 3-5 times, stirred for 16-25 minutes, and the nickel sheet was taken out and dried to obtain a soaked nickel sheet; deionized water was added to the anhydrous ethanol, stirred evenly to obtain an ethanol solution, and the ethanol solution was added to an alcohol lamp as a carbon source, and the soaked nickel sheet was burned for 40-60 minutes to obtain a spiral carbon fiber; The mass ratio of Sn-MOF to anhydrous ethanol is 2.3-2.8:8.0-9.0; In the ethanol solution, the volume proportion of deionized water is 0.25-0.75%; The Sn-MOF preparation method comprises the following steps: dissolving SnCl2·2H2O in 6-8 times the mass of ethanol, stirring evenly to obtain a stannous chloride solution; dissolving 1,2,4-benzenetricarboxylic acid in 8-10 times the mass of dimethylacetamide, stirring evenly to obtain a 1,2,4-benzenetricarboxylic acid solution; dissolving NaOH in 18-22 times the mass of deionized water, stirring evenly to obtain a NaOH solution; mixing the 1,2,4-benzenetricarboxylic acid solution with the NaOH solution, stirring evenly, adding the stannous chloride solution, stirring evenly, and transferring the mixture to a water bath device for water bath reaction, wherein the water bath time is 2.8-3.2 hours, the water bath temperature is 77-83° C., and after the reaction is completed, filtering, washing, and drying to obtain the Sn-MOF; The molar ratio of SnCl2·2H2O, 1,2,4-benzenetricarboxylic acid and NaOH is 1:1.8-2.3:2.7-3.2; (2) Preprocessing The spiral carbon fiber is immersed in the pretreatment liquid for 23-25 hours. After the immersion, the solid is filtered out. The solid is heated to 690-710° C. in an argon atmosphere and kept warm for 3.8-4.2 hours. After the insulation is completed, the solid is naturally cooled to room temperature in an argon atmosphere to obtain a pretreated spiral carbon fiber; The mass ratio of the spiral carbon fiber to the pretreatment liquid is 1:6-10; The pretreatment solution is a mixture of a gadolinium nitrate solution and a nickel chloride solution, wherein the mass ratio of the gadolinium nitrate solution to the nickel chloride solution is 1:0.7-1.2; the concentration of the gadolinium nitrate solution is 0.8-1.2 mol / L, and the concentration of the nickel chloride solution is 0.8-1.2 mol / L.
[0010] 2. Preparation of PI Foam Precursor The pretreated spiral carbon fiber and carbon black are added to N, N-dimethylformamide for ultrasonic oscillation treatment, the ultrasonic time is 25-34 minutes, the ultrasonic frequency is 42-50kHz, and the ultrasonic power is 130-150W. After the ultrasonic treatment, a PI foam precursor is obtained; The mass ratio of the pretreated spiral carbon fiber, carbon black and N,N-dimethylformamide is 5-10:5:85-90.
[0011] 3. Preparation of clear, transparent and viscous solution Anhydrous ethanol, tetrahydrofuran and PI foam precursor are mixed, and after stirring evenly, 3,3',4,4'-benzophenone tetracarboxylic dianhydride is slowly added, and the addition rate is controlled to be 1.8-2.2 g / min. Stirring is continued while adding, and the stirring speed is 90-110 rpm. After the addition is completed, stannous isooctanoate is added, and the temperature is raised to 103-105°C. When it is transparent, the temperature is raised to 118-124°C and kept warm for 0.8-1.3 hours. After the insulation is completed, it is naturally cooled to room temperature, and deionized water, stabilizer, polyethylene glycol, triethanolamine and stannous octoate are added in sequence and stirred. After stirring evenly, the temperature is naturally cooled to room temperature to obtain a clear, transparent and viscous solution; The mass ratio of anhydrous ethanol, tetrahydrofuran, PI foam precursor, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, stannous isooctanoate, deionized water, stabilizer, polyethylene glycol, triethanolamine and stannous octoate is 24.7-25.3:48.0-53.0:24.5-25.5:96-103:0.17-0.22:4.7-5.2:4.8-5.3:0.04-0.06:0.01-0.03:0.02-0.04; The stabilizer is a mixture of γ-aminopropyltriethoxysilane and polydimethylsiloxane, and the mass ratio of the γ-aminopropyltriethoxysilane to the polydimethylsiloxane is 1:0.6-1.3.
[0012] 4. Foaming The clear and transparent viscous solution was mixed evenly with isocyanate PM-200, stirred at 1100-1300 rpm for 14.0-17.0 s, and transferred into a mold for free foaming to obtain primary PI absorption foam; The mass ratio of the clear transparent viscous solution to the isocyanate PM-200 is 245-253:243-255.
[0013] 5. Post-processing The primary PI absorbing foam is allowed to stand for 28-30 minutes, transferred to a microwave device for shaping for 0.8-1.2 hours, and then placed in a 118-123°C vacuum oven for drying for 1.8-2.2 hours to remove the solvent. Finally, it is placed in a high-temperature oven and heated to 246-253°C, kept warm for 2.9-3.2 hours, and then naturally cooled to room temperature to obtain the PI absorbing foam.
[0014] Compared with the prior art, the present invention has achieved beneficial effects: 1. The present invention performs special pretreatment on the spiral carbon fiber and soaks it in a solution containing nickel and rare earth elements to ensure that the rare earth elements and nickel elements can fully penetrate into the spiral carbon fiber, thereby enhancing the strength and thermal stability of the foam. The rare earth doping technology is combined with the excellent performance of the spiral carbon fiber, and the prepared PI absorbing foam has excellent absorbing performance in high frequency bands and wide frequency bands; 2. The PI wave-absorbing foam prepared by the method of the present invention has a compressive strength of 11.2-12.8 MPa, a compressive strength of 9.7-11.4 MPa at 50% compression deformation, and a compressive strength of 10.5-12.2 MPa after being treated at a temperature of 360°C and a pressure of 0.5 MPa for 8.0 h; 3. The PI absorption foam prepared by the method of the present invention has an effective electromagnetic wave absorption frequency band in the frequency range of 2-18 GHz. When the frequency is 5.87 GHz, the reflection loss value is -73.7 dB and the thickness is 0.8 mm. DETAILED DESCRIPTION
[0015] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.
[0016] Example 1 1. Pretreatment of spiral carbon fibers (1) Preparation of spiral carbon fibers 2.3g Sn-MOF was crushed to 140 mesh, mixed with 8.0g anhydrous ethanol, and ultrasonically dispersed to obtain a suspension; a nickel sheet was placed in the suspension 3 times the mass, stirred for 16 minutes, and the nickel sheet was taken out and dried to obtain a soaked nickel sheet; deionized water was added to the anhydrous ethanol, stirred evenly to obtain an ethanol solution, and the ethanol solution was added to an alcohol lamp as a carbon source, and the soaked nickel sheet was burned for 60 minutes to obtain a spiral carbon fiber; In the ethanol solution, the volume proportion of deionized water is 0.25%; The Sn-MOF preparation method comprises the following steps: dissolving SnCl2·2H2O in 6 times the mass of ethanol, stirring evenly to obtain a stannous chloride solution; dissolving 1,2,4-benzenetricarboxylic acid in 10 times the mass of dimethylacetamide, stirring evenly to obtain a 1,2,4-benzenetricarboxylic acid solution; dissolving NaOH in 18 times the mass of deionized water, stirring evenly to obtain a NaOH solution; mixing the 1,2,4-benzenetricarboxylic acid solution with the NaOH solution, stirring evenly, adding the stannous chloride solution, stirring evenly, and transferring the mixture to a water bath device for water bath reaction, wherein the water bath time is 2.8 hours and the water bath temperature is 77° C. After the reaction is completed, filtering, washing, and drying are performed to obtain the Sn-MOF; The molar ratio of SnCl2·2H2O, 1,2,4-benzenetricarboxylic acid and NaOH is 1:1.8:2.7; (2) Preprocessing The spiral carbon fiber was immersed in a pretreatment liquid of 6 times its mass for 23 hours. After the immersion, the solid matter was filtered out. The solid matter was heated to 690° C. in an argon atmosphere and kept warm for 4.2 hours. After the insulation was completed, the solid matter was naturally cooled to room temperature in an argon atmosphere to obtain a pretreated spiral carbon fiber. The pretreatment solution is a mixture of a gadolinium nitrate solution and a nickel chloride solution, wherein the mass ratio of the gadolinium nitrate solution to the nickel chloride solution is 1:0.7; the concentration of the gadolinium nitrate solution is 0.8 mol / L, and the concentration of the nickel chloride solution is 1.2 mol / L.
[0017] 2. Preparation of PI Foam Precursor The pretreated spiral carbon fiber and carbon black were added into N,N-dimethylformamide and subjected to ultrasonic oscillation treatment. The ultrasonic time was 25 min, the ultrasonic frequency was 42 kHz, and the ultrasonic power was 130 W. After the ultrasonic treatment, a PI foam precursor was obtained. The mass ratio of the pretreated spiral carbon fiber, carbon black and N,N-dimethylformamide is 7:5:88.
[0018] 3. Preparation of clear, transparent and viscous solution 24.7g of anhydrous ethanol, 48.0g of tetrahydrofuran and 24.5g of PI foam precursor were mixed, and after stirring, 96g of 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride was slowly added, and the addition rate was controlled to be 1.8g / min. Stirring was continued while adding, and the stirring speed was 90rpm. After the addition was completed, 0.17g of stannous isooctanoate was added, and the temperature was raised to 103°C. When it was transparent, the temperature was raised to 118°C and kept warm for 1.3h. After the insulation was completed, it was naturally cooled to room temperature, and 4.7g of deionized water, 4.8g of stabilizer, 0.04g of polyethylene glycol, 0.01g of triethanolamine and 0.02g of stannous octoate were added in sequence and stirred. After stirring, the temperature was naturally cooled to room temperature to obtain a clear and transparent viscous solution. The stabilizer is a mixture of γ-aminopropyltriethoxysilane and polydimethylsiloxane, and the mass ratio of the γ-aminopropyltriethoxysilane to the polydimethylsiloxane is 1:0.6.
[0019] 4. Foaming 245 g of the clear, transparent viscous solution was mixed evenly with 243 g of isocyanate PM-200, stirred at 1100 rpm for 14.0 s, and transferred into a mold for free foaming to obtain a primary PI absorbent foam.
[0020] 5. Post-processing The primary PI absorbing foam was allowed to stand for 28 minutes, and then transferred to a microwave device for shaping for 0.8 hours. It was then placed in a 118°C vacuum oven for drying for 1.8 hours to remove the solvent. Finally, it was placed in a high-temperature oven and heated to 246°C, kept warm for 3.2 hours, and then naturally cooled to room temperature to obtain the PI absorbing foam.
[0021] The PI absorbing foam prepared by the method of Example 1 has a compressive strength of 11.2 MPa, a compressive strength of 9.7 MPa at 50% compression deformation, and a compressive strength of 10.5 MPa after being treated for 8.0 hours at a temperature of 360°C and a pressure of 0.5 MPa. It has an effective electromagnetic wave absorption frequency band in the frequency range of 2-18 GHz, a reflection loss value of -66.5 dB at a frequency of 5.87 GHz, and a thickness of 0.8 mm.
[0022] Example 2 1. Pretreatment of spiral carbon fibers (1) Preparation of spiral carbon fibers 2.8g Sn-MOF was crushed to 160 mesh, mixed with 9.0g anhydrous ethanol, and ultrasonically dispersed to obtain a suspension; a nickel sheet was placed in the suspension with a mass of 5 times, stirred for 25 minutes, and the nickel sheet was taken out and dried to obtain a soaked nickel sheet; deionized water was added to the anhydrous ethanol, stirred evenly to obtain an ethanol solution, and the ethanol solution was added to an alcohol lamp as a carbon source, and the soaked nickel sheet was burned for 50 minutes to obtain a spiral carbon fiber; In the ethanol solution, the volume proportion of deionized water is 0.50%; The Sn-MOF preparation method comprises the following steps: dissolving SnCl2·2H2O in 6 times the mass of ethanol, stirring evenly to obtain a stannous chloride solution; dissolving 1,2,4-benzenetricarboxylic acid in 10 times the mass of dimethylacetamide, stirring evenly to obtain a 1,2,4-benzenetricarboxylic acid solution; dissolving NaOH in 22 times the mass of deionized water, stirring evenly to obtain a NaOH solution; mixing the 1,2,4-benzenetricarboxylic acid solution with the NaOH solution, stirring evenly, adding the stannous chloride solution, stirring evenly, and transferring the mixture to a water bath device for water bath reaction, wherein the water bath time is 3.2 hours and the water bath temperature is 83° C. After the reaction is completed, filtering, washing, and drying are performed to obtain the Sn-MOF; The molar ratio of SnCl2·2H2O, 1,2,4-benzenetricarboxylic acid and NaOH is 1:2.3:3.2; (2) Preprocessing The spiral carbon fiber was immersed in a pretreatment liquid with a mass of 10 times the mass for 25 hours. After the immersion, the solid matter was filtered out. The solid matter was heated to 710° C. in an argon atmosphere and kept warm for 3.8 hours. After the insulation was completed, the solid matter was naturally cooled to room temperature in an argon atmosphere to obtain a pretreated spiral carbon fiber. The pretreatment solution is a mixture of a gadolinium nitrate solution and a nickel chloride solution, wherein the mass ratio of the gadolinium nitrate solution to the nickel chloride solution is 1:1.2; the concentration of the gadolinium nitrate solution is 1.2 mol / L, and the concentration of the nickel chloride solution is 0.8 mol / L.
[0023] 2. Preparation of PI Foam Precursor The pretreated spiral carbon fiber and carbon black were added into N,N-dimethylformamide and subjected to ultrasonic oscillation treatment. The ultrasonic time was 34 min, the ultrasonic frequency was 50 kHz, and the ultrasonic power was 150 W. After the ultrasonic treatment, a PI foam precursor was obtained. The mass ratio of the pretreated spiral carbon fiber, carbon black and N,N-dimethylformamide is 10:5:90.
[0024] 3. Preparation of clear, transparent and viscous solution 25.3g of anhydrous ethanol, 53.0g of tetrahydrofuran and 25.5g of PI foam precursor were mixed, and after stirring, 103g of 3,3',4,4'-benzophenone tetracarboxylic dianhydride was slowly added, and the addition rate was controlled to be 2.2g / min. Stirring was continued while adding, and the stirring speed was 110rpm. After the addition was completed, 0.22g of stannous isooctanoate was added, and the temperature was raised to 105°C. When it was transparent, the temperature was raised to 124°C and kept warm for 0.8h. After the insulation was completed, it was naturally cooled to room temperature, and 5.2g of deionized water, 5.3g of stabilizer, 0.06g of polyethylene glycol, 0.03g of triethanolamine and 0.04g of stannous octoate were added in sequence and stirred. After stirring, the temperature was naturally cooled to room temperature to obtain a clear and transparent viscous solution. The stabilizer is a mixture of γ-aminopropyltriethoxysilane and polydimethylsiloxane, and the mass ratio of the γ-aminopropyltriethoxysilane to the polydimethylsiloxane is 1:1.3.
[0025] 4. Foaming 253 g of the clear, transparent viscous solution was mixed evenly with 255 g of isocyanate PM-200, stirred at 1300 rpm for 17.0 s, and transferred into a mold for free foaming to obtain a primary PI absorbent foam.
[0026] 5. Post-processing The primary PI absorbing foam was allowed to stand for 30 minutes, and then transferred to a microwave device for shaping for 1.2 hours. It was then placed in a 123°C vacuum oven for drying for 2.2 hours to remove the solvent. Finally, it was placed in a high-temperature oven and heated to 253°C, kept warm for 2.9 hours, and then naturally cooled to room temperature to obtain the PI absorbing foam.
[0027] The PI absorbing foam prepared by the method of Example 2 has a compressive strength of 11.7 MPa, a compressive strength of 10.2 MPa at 50% compression deformation, and a compressive strength of 11.6.2 MPa after being treated in an environment at a temperature of 360°C and a pressure of 0.5 MPa for 8.0 h. It has an effective electromagnetic wave absorption frequency band in the frequency range of 2-18 GHz, a reflection loss value of -68.2 dB at a frequency of 5.87 GHz, and a thickness of 0.8 mm.
[0028] Example 3 1. Pretreatment of spiral carbon fibers (1) Preparation of spiral carbon fibers 2.5g Sn-MOF was crushed into 150 meshes, mixed with 8.3g anhydrous ethanol, and ultrasonically dispersed to obtain a suspension; a nickel sheet was placed in the suspension of 4 times the mass, stirred for 20 minutes, and the nickel sheet was taken out and dried to obtain a soaked nickel sheet; deionized water was added to the anhydrous ethanol, stirred evenly to obtain an ethanol solution, and the ethanol solution was added to an alcohol lamp as a carbon source, and the soaked nickel sheet was burned for 40 minutes to obtain a spiral carbon fiber; In the ethanol solution, the volume proportion of deionized water is 0.75%; The Sn-MOF preparation method comprises the following steps: dissolving SnCl2·2H2O in 8 times the mass of ethanol, stirring evenly to obtain a stannous chloride solution; dissolving 1,2,4-benzenetricarboxylic acid in 8 times the mass of dimethylacetamide, stirring evenly to obtain a 1,2,4-benzenetricarboxylic acid solution; dissolving NaOH in 20 times the mass of deionized water, stirring evenly to obtain a NaOH solution; mixing the 1,2,4-benzenetricarboxylic acid solution with the NaOH solution, stirring evenly, adding the stannous chloride solution, stirring evenly, and transferring the mixture to a water bath device for water bath reaction, wherein the water bath time is 3.0 hours and the water bath temperature is 80° C. After the reaction is completed, filtering, washing, and drying are performed to obtain the Sn-MOF; The molar ratio of SnCl2·2H2O, 1,2,4-benzenetricarboxylic acid and NaOH is 1:2:3; (2) Preprocessing The spiral carbon fiber was immersed in a pretreatment liquid of 8 times its mass for 24 hours. After the immersion, the solid matter was filtered out. The solid matter was heated to 700° C. in an argon atmosphere and kept warm for 4.0 hours. After the insulation was completed, the solid matter was naturally cooled to room temperature in an argon atmosphere to obtain a pretreated spiral carbon fiber. The pretreatment solution is a mixture of a gadolinium nitrate solution and a nickel chloride solution, the mass ratio of the gadolinium nitrate solution to the nickel chloride solution is 1:1; the concentration of the gadolinium nitrate solution is 1.0 mol / L, and the concentration of the nickel chloride solution is 1.0 mol / L.
[0029] 2. Preparation of PI Foam Precursor The pretreated spiral carbon fiber and carbon black were added into N,N-dimethylformamide and subjected to ultrasonic oscillation treatment. The ultrasonic time was 30 min, the ultrasonic frequency was 46 kHz, and the ultrasonic power was 140 W. After the ultrasonic treatment, a PI foam precursor was obtained. The mass ratio of the pretreated spiral carbon fiber, carbon black and N,N-dimethylformamide is 5:5:85.
[0030] 3. Preparation of clear, transparent and viscous solution 25.0g of anhydrous ethanol, 50.0g of tetrahydrofuran and 25.0g of PI foam precursor were mixed, and after stirring, 100g of 3,3',4,4'-benzophenone tetracarboxylic dianhydride was slowly added, and the addition rate was controlled to be 2.0g / min. Stirring was continued while adding, and the stirring speed was 100rpm. After the addition was completed, 0.20g of stannous isooctanoate was added, and the temperature was raised to 100°C. When it was transparent, the temperature was raised to 120°C and kept warm for 1.0h. After the insulation was completed, it was naturally cooled to room temperature, and 5.0g of deionized water, 5.0g of stabilizer, 0.05g of polyethylene glycol, 0.02g of triethanolamine and 0.03g of stannous octoate were added in sequence and stirred. After stirring, the temperature was naturally cooled to room temperature to obtain a clear and transparent viscous solution. The stabilizer is a mixture of γ-aminopropyltriethoxysilane and polydimethylsiloxane, and the mass ratio of the γ-aminopropyltriethoxysilane to the polydimethylsiloxane is 1:1.
[0031] 4. Foaming 250 g of the clear, transparent viscous solution was mixed evenly with 250 g of isocyanate PM-200, stirred at 1200 rpm for 15.0 s, and transferred into a mold for free foaming to obtain a primary PI absorbent foam.
[0032] 5. Post-processing The primary PI absorbing foam was allowed to stand for 25 minutes, and then transferred to a microwave device for shaping for 1 hour, and then placed in a 120°C vacuum oven for drying for 2 hours to remove the solvent, and finally placed in a high-temperature oven to raise the temperature to 250°C, keep the temperature for 3 hours, and wait until it naturally cooled to room temperature to obtain the PI absorbing foam.
[0033] The PI absorbing foam prepared by the method of Example 3 has a compressive strength of 12.8 MPa, a compressive strength of 11.4 MPa at 50% compression deformation, and a compressive strength of 12.2 MPa after being treated in an environment at a temperature of 360°C and a pressure of 0.5 MPa for 8.0 h. It has an effective electromagnetic wave absorption frequency band in the frequency range of 2-18 GHz, a reflection loss value of -73.7 dB at a frequency of 5.87 GHz, and a thickness of 0.8 mm.
[0034] Unless otherwise specified, all ratios and percentages described in the present invention are by mass ratios and percentages are by mass percentages.
[0035] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a rare earth element-doped PI microwave-absorbing foam, characterized in that: It includes the steps of pre-treatment of spiral carbon fiber, preparation of PI foam precursor, preparation of clear transparent viscous solution, foaming and post-treatment; The pretreatment step of the spiral carbon fiber includes the steps of preparing the spiral carbon fiber and pretreatment; The pretreatment step comprises soaking the spiral carbon fiber in a pretreatment liquid, filtering out solid matter, and heat-treating the solid matter under an argon atmosphere to obtain a pretreated spiral carbon fiber; The pretreatment solution is a mixture of a gadolinium nitrate solution and a nickel chloride solution; The step of preparing the clear and transparent viscous solution is as follows: anhydrous ethanol, tetrahydrofuran and a PI foam precursor are mixed, and after being stirred evenly, 3,3',4,4'-benzophenone tetracarboxylic dianhydride is added, and the adding rate is controlled to be 1.8-2.2 g / min, and the stirring speed is 90-110 rpm during the addition, and then stannous isooctanoate is added, and the temperature is increased to 103-105° C. When a transparent state is presented, the temperature is increased to 118-124° C., and the temperature is kept for 0.8-1.3 hours, and then the temperature is reduced to room temperature, and deionized water, a stabilizer, polyethylene glycol, triethanolamine and stannous octoate are added in sequence, and stirred evenly to obtain a clear and transparent viscous solution.
2. The method for preparing a rare earth element-doped PI microwave absorbing foam according to claim 1, characterized in that: The pretreatment step comprises soaking the spiral carbon fiber in a pretreatment liquid for 23-25 hours, filtering out solid matter after the soaking, heating the solid matter to 690-710° C. in an argon atmosphere, and keeping the temperature for 3.8-4.2 hours. After the heat preservation is completed, naturally cooling the solid matter to room temperature in an argon atmosphere to obtain a pretreated spiral carbon fiber; The mass ratio of the spiral carbon fiber to the pretreatment liquid is 1:6-10; The pretreatment solution is a mixture of a gadolinium nitrate solution and a nickel chloride solution, wherein the mass ratio of the gadolinium nitrate solution to the nickel chloride solution is 1:0.7-1.2; the concentration of the gadolinium nitrate solution is 0.8-1.2 mol / L, and the concentration of the nickel chloride solution is 0.8-1.2 mol / L.
3. The method for preparing a rare earth element-doped PI microwave absorbing foam according to claim 1, characterized in that: The steps of preparing the spiral carbon fiber are as follows: crushing Sn-MOF to 140-160 mesh, mixing with anhydrous ethanol, and uniformly dispersing by ultrasonication to obtain a suspension; placing a nickel sheet in the suspension with a mass of 3-5 times, stirring for 16-25 minutes, taking out the nickel sheet and drying it to obtain an immersed nickel sheet; adding deionized water to the anhydrous ethanol, stirring evenly to obtain an ethanol solution, adding the ethanol solution as a carbon source to an alcohol lamp, burning the immersed nickel sheet for 40-60 minutes, and obtaining the spiral carbon fiber; The mass ratio of Sn-MOF to anhydrous ethanol is 2.3-2.8:8.0-9.0; In the ethanol solution, the volume proportion of deionized water is 0.25-0.75%.
4. The method for preparing a rare earth element-doped PI microwave absorbing foam according to claim 3, characterized in that: The Sn-MOF preparation method comprises the following steps: dissolving SnCl2·2H2O in 6-8 times the mass of ethanol, stirring evenly to obtain a stannous chloride solution; dissolving 1,2,4-benzenetricarboxylic acid in 8-10 times the mass of dimethylacetamide, stirring evenly to obtain a 1,2,4-benzenetricarboxylic acid solution; dissolving NaOH in 18-22 times the mass of deionized water, stirring evenly to obtain a NaOH solution; mixing the 1,2,4-benzenetricarboxylic acid solution with the NaOH solution, stirring evenly, adding the stannous chloride solution, stirring evenly, and transferring the mixture to a water bath device for water bath reaction, wherein the water bath time is 2.8-3.2 hours, the water bath temperature is 77-83° C., and after the reaction is completed, filtering, washing, and drying to obtain the Sn-MOF; The molar ratio of SnCl2·2H2O, 1,2,4-benzenetricarboxylic acid and NaOH is 1:1.8-2.3:2.7-3.
2.
5. The method for preparing a rare earth element-doped PI microwave absorbing foam according to claim 1, characterized in that: The step of preparing the PI foam precursor is to add the pretreated spiral carbon fiber and carbon black into N,N-dimethylformamide, and perform ultrasonic oscillation treatment, wherein the ultrasonic time is 25-34 minutes, the ultrasonic frequency is 42-50kHz, and the ultrasonic power is 130-150W. After the ultrasonic treatment, the PI foam precursor is obtained; The mass ratio of the pretreated spiral carbon fiber, carbon black and N,N-dimethylformamide is 5-10:5:85-90.
6. The method for preparing a rare earth element-doped PI microwave absorbing foam according to claim 1, characterized in that: In the step of preparing the clear and transparent viscous solution, the mass ratio of the anhydrous ethanol, tetrahydrofuran, PI foam precursor, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, stannous isooctanoate, deionized water, stabilizer, polyethylene glycol, triethanolamine and stannous octoate is 24.7-25.3:48.0-53.0:24.5-25.5:96-103:0.17-0.22:4.7-5.2:4.8-5.3:0.04-0.06:0.01-0.03:0.02-0.04; The stabilizer is a mixture of γ-aminopropyltriethoxysilane and polydimethylsiloxane, and the mass ratio of the γ-aminopropyltriethoxysilane to the polydimethylsiloxane is 1:0.6-1.
3.
7. The method for preparing a rare earth element-doped PI microwave absorbing foam according to claim 1, characterized in that: The foaming step comprises mixing the clear transparent viscous solution and the isocyanate PM-200 evenly, stirring at 1100-1300 rpm for 14.0-17.0 seconds, and transferring the mixture into a mold for free foaming to obtain a primary PI absorption foam; The mass ratio of the clear transparent viscous solution to the isocyanate PM-200 is 245-253:243-255.
8. The method for preparing a rare earth element-doped PI microwave absorbing foam according to claim 1, characterized in that: The post-treatment step is to place the primary PI absorbing foam at rest for 28-30 minutes, transfer it to a microwave device for shaping for 0.8-1.2 hours, then place it in a 118-123° C. vacuum oven for drying for 1.8-2.2 hours to remove the solvent, and finally place it in a high-temperature oven to raise the temperature to 246-253° C., keep it warm for 2.9-3.2 hours, and wait for it to naturally cool to room temperature to obtain the PI absorbing foam.
Citation Information
Patent Citations
Preparation method of foam with electromagnetic impedance gradient double-gradient structure
CN114773657A
Porous materials embedded with nanoparticles, methods of fabrication and uses thereof
US20100231433A1